Photonic Multiple Microwave Frequency Measurement Based on Frequency-to-Time Mapping - Feng Zhou; Hao Chen; Xu Wang; Linjie Zhou; Jianji Dong; Xinliang Zhang (IEEE Photonics Journal, 2018)
A photonic multiple microwave frequency measurement system is presented and demonstrated based on a swept frequency silicon microring resonator (MRR). The drop-port of a high-Q MRR is employed as a periodic narrowband scanning filter driven by a sawtooth voltage signal. The unknown frequency can be mapped to time interval between pulse appearances when scanning the modulated signal and the frequency-to-time mapping is established. In the experiments, we obtain a measurement range of 25 GHz with an error of ±510 MHz. Meanwhile, the measurement resolution for multi-frequency measurement is about 5 GHz. Our scheme offers a simple structure, low-cost solution, capability of multiple frequency measurement, and potential of chip-integration.